Hodnocení finanční situace podniku a návrhy na její zlepšení - Janyšková, Radka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Hodnocení současné finanční situace podniku je v bakalářské práci založeno na finanční analýze. Data pro finanční analýzu byla poskytnuta firmou. Součástí bakalářské práce jsou doporučení pro zlepšení finanční situace. Finanční analýza byla provedena pro pětileté období.

Evaluation of curent financial situation in the company in bachelor’s thesis is based on financial analysis. Materials for financial analysis were provided by the company. The proposals to improvement the financial situation are included in the thesis. The financial analysis was made for the period of five years.
Evaluation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: zhodnocení finanční situace podniku; finanční analýza; absolutní ukazatele; rozdílové ukazatele; tokové ukazatele; poměrové ukazatele; soustavy ukazatelů; evaluation of curent financial situation; financial analysis; absolute indicators; differential indicators; flow indicators; ratio indicators; systems of indicators